2001
DOI: 10.1016/s0953-7562(08)61968-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies on intraspecific diversity and phylogenetic position of Coniothyrium minitans

Abstract: Simple sequence repeat (SSR)-PCR amplification using a microsatellite primer (GACA) % and ribosomal RNA gene sequencing were used to examine the intraspecific diversity in the mycoparasite Coniothyrium minitans based on 48 strains, representing eight colony types, from 17 countries world-wide. Coniothyrium cerealis, C. fuckelii and C. sporulosum were used for interspecific comparison. The SSR-PCR technique revealed a relatively low level of polymorphism within C. minitans but did allow some differentiation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…(Cui et al, 2000), Arabidopsis thaliana (L.) Heynh. (Baud et al, 2002;Ludwig-Mül-ler, 2007) and Coniothyrium minitans W. A. Campbell (Muthumeenakshi et al, 2001). Hence, this kind of ecotypes can be called genetic differentiation (Hufford and Mazer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Cui et al, 2000), Arabidopsis thaliana (L.) Heynh. (Baud et al, 2002;Ludwig-Mül-ler, 2007) and Coniothyrium minitans W. A. Campbell (Muthumeenakshi et al, 2001). Hence, this kind of ecotypes can be called genetic differentiation (Hufford and Mazer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…de Bary, an omniovorous plant pathogenic fungus. Muthumeenakshi et al (2001) reported that C. minitans is closely related to ascomycetous fungi based on phylogenetic analysis of DNA sequences of internal transcribed spacer regions (ITS1 and ITS2) and the 5.8S rRNA gene. Numerous studies showed that C. minitans is a promising biocontrol agent of S. sclerotiorum (de Vrije et al 2001;Whipps et al 2008), Sclerotinia minor Jagg.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous phenotypes differing in colony morphology and a number of other biological characteristics (Sandys-Winsch et al 1993;Jones and Stewart 2000;Grendene et al 2002) but ability to parasitize sclerotia of S. sclerotiorum remains a key feature. Some isolates have begun to be characterised using molecular procedures such as random amplification of polymorphic DNA (RAPD) and simple sequence repeat (SSR) -PCR profiling, and rRNA gene sequencing (Goldstein et al 2000;Ridgway and Stewart 2000;Muthumeenakshi et al 2001;Grendene et al 2002). Recently, based on anamorphic characteristics seen in vitro, and maximum parsimony analysis of ITS and SSU nrDNA sequences, C. minitans was reclassified as Paraconiothyrium minitans (Verkley et al 2004).…”
Section: Introductionmentioning
confidence: 99%